GRAPPLING WITH THE STRUCTURAL FROM A SITUATED PERSPECTIVE - Busch-Jensen, Peter (PINS-Psychology in Society, 2025)
The aims of this article are threefold. Firstly, the article is an attempt to contribute to discussions about what a Marxist psychology might look like, from an impression of Marx and Marxism generally having much too little to say about people’s everyday lives and the situated and practical aspects of people’s mental life. Secondly, the article links this discussion to the relationship between method and critical thinking and the importance of a critical position that does not voice critique from some potentially totalizing platform, nor from some detached position of “nowhere”. The former is a risk in much Marxist theorizing. The latter is a risk in much post-structuralist critique, as discussed in relation to the work of Michel Foucault. Finally, taking a point of departure in an empirical example and ideas from German-Danish critical psychology, the text’s overall ambition is to outline and discuss how a subject-scientific psychology can include and develop its attention to the organizational, structural and political dimensions of people’s everyday lives.